X-y=c(X)

Simple and best practice solution for X-y=c(X) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-y=c(X) equation:


Simplifying
X + -1y = c(X)

Multiply c * X
X + -1y = cX

Solving
X + -1y = cX

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1cX' to each side of the equation.
X + -1cX + -1y = cX + -1cX

Combine like terms: cX + -1cX = 0
X + -1cX + -1y = 0

Add 'y' to each side of the equation.
X + -1cX + -1y + y = 0 + y

Combine like terms: -1y + y = 0
X + -1cX + 0 = 0 + y
X + -1cX = 0 + y
Remove the zero:
X + -1cX = y

Combine like terms: y + -1y = 0
X + -1cX + -1y = 0

The solution to this equation could not be determined.

See similar equations:

| 4x+14=9x-35 | | 2y^2+6y+5=0 | | 2(m+3)=4m-k | | 7x-6=-2x+3 | | 9-5x^2=-71 | | 11x+2=14x-7 | | y=2x+1(X) | | 2(2x-4)=-20 | | 94.9536=20.3472+11.304h | | 15-(-42)= | | 880=2n^2-4n | | 1672.992=2*3.14*r^2+2*3.14*7.2*h | | 5(x+7)-6(x+6)=0 | | N^2=8n-16 | | t=2m(m) | | 3(5)+7(-6)= | | 1x-3=3x-13 | | y-6=2y-15 | | -5(-3p-4)=-70 | | 5-4(x-2)=12x-3 | | 24=2(v+2)+2v | | 2x+(-6)=3(2x-10) | | b^2+6b=-5 | | 8.1x-3.7=2.4x+2 | | 5x+16=5-5 | | 3(2-5m)=81 | | (-3+6i)(1+i)= | | P-19=34 | | -38=3(y-6)+2y | | 4x-7=4(x-3)+5 | | 8/n=12/15 | | 16x-7=13x+2 |

Equations solver categories